On the lie’s truth and the truth’s lie - Güendel Angulo, Herman (2017)
This essay explores the topic of the lie and the truth as a problem resulting from a prejudiced interpretation of their presence in our daily relationships and social organization. It proposes the acceptance of a new type of approach in order to overcome this superstructural knot, which, as apposed to being moral and formally logical, is rather epochal, epistemological, erotic and contextual.